Czynniki konkurencyjności regionów - ich klasyfikacje oraz znaczenie - Markowska-Przybyła, Urszula (Factors of Regions' Competitiveness - Their Classifications and Significance, 2005)
The term „competitiveness” becomes actually often a point of reference to making synthetic estimates that are designed for the comparison of various units between themselves, also spatial units. The subject of comparison are also factors that determine competitiveness. The aim of the article is to define factors, symptoms and conditions of competitiveness, their classification and to specify the most important of them.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1095, s. 11-22